(3QSGdI aj CaYGd GdYHGOs - (3GdUGOb GdbjUQjs ((3CMeO Hf CMeO GdeYQha HSQGL s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GYde Cf ai CaYGd GdYHGO SHYI ePGgH Hd KeGfjI ePGgH dCfg EeG Cf dGjchf ajgG ddYHO eONdkG GUdkG HCf dGjchf ddYHO bOQI s
(3BNQgG (B:s
(3hCeG ePgH GdKGef aEf jbGd EfG fYde hfMRe Cf ddYHO eONdkG ai aYdg hdcf dGfYde HCi hLg hWQjb UdhG Ydi SjO GdCfGe cJGHJi ai GdSMQ hGdfGS jfGe ef GdBKGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , LeYjI GdebGUO GdESdGejI (B- (3eYgO GdOQGSGJ GdESdGejI (B((3Yde GdcdGe (B5/243) s
Keywords: (3GdJhMjO hGdedd hGdfMds